Head and face masks in Navaho ceremonialism - Haile, Berard, 1874-1961 (University of Utah Press, 1996)
"Father Berard Haile (d. 1955) spent a lifetime studying and recording Navajo ceremonial practices. His ethnographic work was held in wide regard by contemporary anthropologists, and he is still commonly cited by present-day students of Navajo ceremonialism." "Originally issued in a limited edition in 1947, Head and Face Masks in Navaho Ceremonialism presents information on masks and their uses, most of it obtained in 1908 from one family of singers and supplemented over the following forty years. It offers a detailed account of the necessary attributes of Navajo masks and their construction. At the heart of the book is a day-by-day account of the nine-day Nightway healing practice, now the primary ceremony in which masks are used. There is also a discussion of two masks Haile attributes to the Upward Reaching Way, no longer practiced. An addendum by Robert Young updates Haile's Navajo orthography." "In this work, Haile reports what he was told with a minimum of interpretation, assumption, or opinion. The result is a Navajo account of the origin of the ye'ii or Holy People whom the masks and associated sand paintings personify."--Jacket